An economic analysis of the relationship between stock returns and the anticipated and unanticipated money growth: the case of Malaysia - Mohamed, Azali; Habibullah, Muzafar Shah; Baharumshah, Ahmad Zubaidi (Universiti Utara Malaysia, 1999)
This paper investigates the relationship between stock returns and both the anticipated and unanticipated components of money supply growth using quarterly data for the period 1978:l-1997:4. The objective of the paper is to determine whether the components of both, narrow (MI) and broad (M2) money supply growth has been incorporated in the movements of stock returns. Using the Barro two-step procedure, our results suggest that the efficient market hypothesis for the KLSE cannot be rejected with respect to both narrow and broad money components.